The economics of the food system revolution - Reardon, Thomas; Timmer, Peter C. (Annual Reviews, 2012)
A revolution in food systems—food supply chains upstream from farms, to the food industry in the midstream segments of processing and wholesale and in the downstream segment of retail, then on to consumers—has been under way in the United States for more than a century and in developing countries for more than three decades. The transformation includes extensive consolidation, very rapid institutional and organizational change, and progressive modernization of the procurement system. In this article we examine the economics of these system-wide changes. We argue that the steps of conceptualizing and empirically researching this transformation—its patterns and trends, determinants, and impacts on farms and processing small and micro enterprises—are still in their infancy because of (a) remaining limitations on data suitable for formal modeling and hypothesis testing and (b) the sheer complexity of food system–related decisions that need to be modeled and understood. With the rapid accumulation of high-quality data now under way, conceptual and theoretical progress is also likely to be rapid.